RELIABILITY-BASED NUMERICAL MODELING FOR INVESTIGATION OF THE IMPACT OF PRINTING PARAMETERS ON BUILDABILITY OF 3D PRINTED CONCRETE STRUCTURES - Zede (Zede Journal of Ethiopian Engineers and Architects, 2024)
The significance of 3D concrete printing (3DCP) as an additive manufacturing technology has increased over the past few years. Both academic research studies and large-scale industrial realizations of 3DCP have shown that it represents a viable alternative to traditional concrete mold casting. The key reason for this rapid development is that urgent challenges of the construction sector, in particular sustainability and productivity, are addressed. However, previous studies on technological progress have mainly been experimentally driven. The introduction of appropriate numerical modeling techniques would, therefore, further foster the success of 3DCP by providing insight into the structural behavior, which is beyond experimental possibilities. The present study introduces a numerical modeling technique for the analysis of 3DCP wall structures using a time-dependent reliability analysis. Uncertainties occurring throughout the printing process and time dependent properties of printable concreteare considered. In addition, sensitivity analysis of random variables is done, which could be used as indicative preference for future process optimizations.The results yield valuable insight into the influence of printing process parameters on the failure of 3D printed concrete structures. The numerical model predicts build ability of a 3D printed concrete wall structure as it is in very good agreement with experimental results of similar studies.